Neoproterozoic mafic complex in the Bikou microblock on the northwestern Yangtze Block: Implications for mantle source and tectonic evolution - Li Qin; Xianzhi Pei; Ruibao Li; Lei Pei; Chengjun Liu; Zuochen Li; Shaowei Zhao; Feng Gao (Lithos, 2026)

Microplastisphere as a crowded and inclusive micro-ecosystem in seagrass meadow: Cross-kingdom connections and microbial food web - Qiqi Wu; Yu Xia; Yiwei Tao; Chengjun Ge; Yuanyuan Zhao; Dan Feng; Hui Deng (Marine Pollution Bulletin, 2026)

Dark side of biodegradable microplastics in mangrove ecosystem: Plastisphere as an overlooked hotspot of sulfate-reducing metabolism - Yiqiao Zheng; Qiqi Wu; Yu Xia; Hui Deng; Yuanyuan Zhao; Jiwei Luo; Dan Feng; Chengjun Ge (Water Research, 2026)

CYP4G paralog divergence underlies pest resilience to insecticides and warming climate - Huiling Zhou; Shuyan Feng; Meiqi Chen; Meiqian Zhang; Yusi Li; Chengjun Li; Bin Li (Insect Biochemistry and Molecular Biology, 2026)

Microplastics drive the reconfiguration of microbial sulfur cycling pathways in seagrass bed sediments - Mingguang Luo; Jinluo Fan; Xiujun Wang; Yibing Ge; Dan Feng; Shengkai Cao; Jun Wang; Hui Deng; Jiwei Luo; Yuanyuan Zhao; Chengjun Ge; Honglin Bu (Environmental Pollution, 2026)

Tonian intra-oceanic subduction initiation at the northwestern Yangtze Block: Evidence from forearc ophiolite fragments in the Bikou microblock - Li Qin; Xianzhi Pei; Ruibao Li; Lei Pei; Chengjun Liu; Zuochen Li; Shaowei Zhao; Feng Gao (Precambrian Research, 2026)

In-situ stress measurements over the Eastern Himalayan syntaxis and implications for seismicity - Xianghui Qin; Chongyuan Zhang; Derek Elsworth; Wen Meng; Zhihao Liang; Chengjun Feng; Yuehui Yang; Dongsheng Sun (Tectonophysics, 2025)

DOM from eco-friendly fertilizers increases soil potential pathogen risk and shapes specific microbial populations under sprinkler and drip irrigation - Jinluo Fan; Rui Song; Heng Luo; Haijun Wu; Dongming Wu; Jun Wang; Yanqun Guo; Shuailing Hou; Mingguang Luo; Guoliang Ren; Hui Deng; Jiwei Luo; et al. (Applied Soil Ecology, 2025)

Effect of layered grinding on the distribution and binding forms of protein and polyphenols in highland barley bran - Muyan Ma; Feng Liang; Wenju Zhou; Pin Ma; Chengjun Ji; Yan Du; Zhaoxin Tu; Li Wang; Xinxia Zhang; Ting Li; Juan Li (Food Bioscience, 2025)

Comprehensive review on in vitro bioaccessibility of mercury in various foodstuffs - Yu Gong; Chengjun Li; Fei He; Feng Ge; Yongming Ju; Huan Zhong; Weixin Li (Journal of Hazardous Materials, 2025)

Colonization time of plastisphere drives the dynamics of organic carbon stability and microbial communities in seagrass bed sediments - Shuailing Hou; Jun Wang; Dan Feng; Dongming Wu; Shiquan Chen; Jinluo Fan; Mingguang Luo; Hui Deng; Xing Yang; Jiwei Luo; Yuanyuan Zhao; Chengjun Ge (Journal of Hazardous Materials, 2025)

High-Resolution 3D Shear-Wave velocity structure in xiong’an New Area, Beijing (China), revealed by short-period dense seismic array - Qiaoxia Liu; Zhiping Xu; Ming Zhou; Yonghong Duan; Yong Qiu; Chengjun Feng; Shuaipeng Zhu; Chongpeng Wang; Minjie Chen (Journal of Asian Earth Sciences, 2025)

Coseismic surface deformation and source mechanism of the 2023 Ms 6.2 Jishishan earthquake, northeastern Tibetan Plateau - Peng Chen; Siqi Shu; Zhonghai Wu; Tao Wang; Chengjun Feng; Jiamei Liu; Shuai Zhang; Haojie Wang; Kun Li (Journal of Structural Geology, 2024)

Detrital Zircon Geochronology of Early Triassic Strata in the West Qinling Orogen: Implications for the Tectonic Evolution of the Paleo-Tethyan Ocean - Zuochen Li; Xianzhi Pei; Liyong Wei; Guobing Liang; Meng Wang; Ruibao Li; Lei Pei; Chengjun Liu; Youxin Chen; Feng Gao (Journal of Earth Science, 2024)

Distribution, sources and ecological risks of per- and polyfluoroalkyl substances in overlying water and sediment from the mangrove ecosystem in Hainan Island, China - Guoliang Ren; Like Chen; Jinluo Fan; Shuailing Hou; Junnan Chen; Hui Deng; Jiwei Luo; Peng Huang; Yuanyuan Zhao; Jiatong Li; Dan Feng; Chengjun Ge; et al. (Science of The Total Environment, 2024)

Convergence of soil bacterial communities with time and reduction of bacterial interaction complexity in response to meso- and microplastic stress - Lin Yue; Yangbo Liu; Guanhui Li; Hui Deng; Yuanyuan Zhao; Dan Feng; Hongfei Sun; Huamei Yu; Chengjun Ge; Haiying Chen (Journal of Environmental Chemical Engineering, 2023)

Efficient ternary organic solar cells enabled by asymmetric nonfullerene electron acceptor with suppressed nonradiative recombination - Renjie Xu; Yuanyuan Jiang; Feng Liu; Wenli Su; Wuyue Liu; Shengjie Xu; Haijun Fan; Chengjun Jiang; Qianshou Zong; Wenkai Zhang; Xiaozhang Zhu (Chemical Engineering Journal, 2023)

Mangrove degradation retarded microplastics weathering and affected metabolic activities of microplastics-associated microbes - Hui Deng; Yuqing Zhang; Dazhen Li; Qianqian Fu; Jianxiong He; Yuanyuan Zhao; Dan Feng; Huamei Yu; Chengjun Ge (Journal of Hazardous Materials, 2023)

Response of earthworms to microplastics in soil under biogas slurry irrigation: Toxicity comparison of conventional and biodegradable microplastics - Yuanyuan Zhao; Huiting Jia; Hui Deng; Wenzhe Xing; Dan Feng; Jiatong Li; Chengjun Ge; Huamei Yu; Ying Zhang; Haiying Chen (Science of The Total Environment, 2023)

Intensified gas-phase hydrogenation of acetone to isopropanol catalyzed at metal-oxide interfacial sites - Kun Liu; Yongbin Sun; Jie Feng; Yang Liu; Jian Zhu; Chengjun Han; Changzhi Chen; Tianyi Bao; Xiaoqun Cao; Xiaomin Zhao; Yong Yang; Guofeng Zhao (Chemical Engineering Journal, 2023)

Research on the Karhunen–Loève Transform Method and Its Application to Hull Form Optimization - Haichao Chang; Chengjun Wang; Zuyuan Liu; Baiwei Feng; Chengsheng Zhan; Xide Cheng (Journal of Marine Science and Engineering, 2023)
Hull form optimization becomes prone to the curse of dimensionality as the number of design variables increases. The traditional sensitivity analysis method requires massive computational fluid dynamics (CFD) computations and analyzing the effects of all variables on the output; thus, it is extremely time-consuming. Considering this, the development of a rapid and effective dimensionality reduction method is particularly important. The Karhunen–Loève (K–L) transform method projects data from a high-dimensional space onto a low-dimensional space in the direction of the eigenvectors corresponding to large-variance eigenvalues. It extracts the principal components that represent the hull offset information to represent the hull geometric characteristics by analyzing the relationship between the variables in the sample offset matrix. The geometric information matrices of new hull forms can be rapidly reconstructed from the principal components. Compared with direct optimization methods, fewer variables are used to control the deformation of the hull form from the perspective of geometric deformation, avoid a large number of CFD calculations, and improve the efficiency of optimization. This study examined the relevant K–L matrix solution methods and the corresponding hull form reconstruction methods and proposed eigenvalue-based hull form reconstruction equations. The K–L transform method was combined with a previously developed multidisciplinary platform for a comprehensive optimization of ship hydrodynamic performance for hull form optimization, and its effectiveness was verified by using it to optimize DTMB 5415. The results showed that the K–L transform–based dimensionality reduction method significantly reduces the time consumption of optimization while maintaining an acceptable optimization performance.

Interactive effects of high temperature and crude protein levels on growth performance, nitrogen excretion, and fecal characteristics of broilers - Quanwei Liu; Jinghai Feng; Limin Wei; Chengjun Hu; Xinli Zheng; Ruiping Sun; Minhong Zhang (Tropical Animal Health and Production, 2022)

Dynamic response of the inhomogeneous pavement structure containing a buried fault zone under the moving aircraft loads - Jiawei Wan; Bin Li; Yang Gao; Chengxuan Tan; Chengjun Feng; Peng Zhang (Bulletin of Engineering Geology and the Environment, 2022)

Above- and belowground biomass allocation and its regulation by plant density in six common grassland species in China - Yuanfeng Sun; Yupin Wang; Zhengbing Yan; Luoshu He; Suhui Ma; Yuhao Feng; Haojie Su; Guoping Chen; Yinping Feng; Chengjun Ji; Haihua Shen; Jingyun Fang (Journal of Plant Research, 2022)

Soil carbon persistence governed by plant input and mineral protection at regional and global scales - Leiyi Chen; Kai Fang; Bin Wei; Shuqi Qin; Xuehui Feng; Tianyu Hu; Chengjun Ji; Yuanhe Yang (Ecology Letters, 2021)
Elucidating the processes underlying the persistence of soil organic matter (SOM) is a prerequisite for projecting soil carbon feedback to climate change. However, the potential role of plant carbon input in regulating the multi‐layer SOM preservation over broad geographic scales remains unclear. Based on large‐scale soil radiocarbon (∆ 14 C) measurements on the Tibetan Plateau, we found that plant carbon input was the major contributor to topsoil carbon destabilisation despite the significant associations of topsoil ∆ 14 C with climatic and mineral variables as well as SOM chemical composition. By contrast, mineral protection by iron–aluminium oxides and cations became more important in preserving SOM in deep soils. These regional observations were confirmed by a global synthesis derived from the International Soil Radiocarbon Database (ISRaD). Our findings illustrate different effects of plant carbon input on SOM persistence across soil layers, providing new insights for models to better predict multi‐layer soil carbon dynamics under changing environments.

Geochemistry and tectonic setting of Middle Ordovician MORB-like basalts in the Kunlun Orogen: implications for a back-arc environment - Ruibao Li; XianZhi Pei; Zuochen Li; Lei Pei; Youxin Chen; Chengjun Liu; Guochao Chen; Keng Feng (Arabian Journal of Geosciences, 2021)

Experimental investigation of the influence of bedding planes on the mechanical characteristics of saturated sand - Zhen Tang; Qiang Luo; Chengjun Feng; Siyu Zhu (Bulletin of Engineering Geology and the Environment, 2021)

Characteristics and main causes of earth fissures in northeastern Beijing Plain, China - Jiawei Wan; Bin Li; Chengxuan Tan; Chengjun Feng; Peng Zhang; Bangshen Qi (Bulletin of Engineering Geology and the Environment, 2020)

Occurrence and photodegradation of methylmercury in surface water of Wen-Rui-Tang River network, Wenzhou, China - Shuihong Pan; Chuchu Feng; Jialu Lin; Lidong Cheng; Chengjun Wang; Yuegang Zuo (Environmental Science and Pollution Research, 2017)

Co-seismic and post-seismic effects of the Tohoku-Oki M W 9.0 earthquake in North and Northeast China - Chengjun Feng; Peng Zhang; Chengxuan Tan; Bangshen Qi; Lianjie Wang (Journal of Seismology, 2016)

The stress state of the Beichuan-Jiangyou segment of the Longmenshan fault before and after the Wenchuan M S 8.0 Earthquake - Chengjun Feng; Qunce Chen; Chengxuan Tan; Xianghui Qin; Peng Zhang; Wen Meng (Journal of Earth Science, 2014)

Crustal stress state and seismic hazard along southwest segment of the Longmenshan thrust belt after Wenchuan Earthquake - Xianghui Qin; Chengxuan Tan; Qunce Chen; Manlu Wu; Chengjun Feng (Journal of Earth Science, 2014)

Influence of limited soil on the root distribution and anchorage of Vitex negundo L. - Feng Long; Shaocai Li; Hailong Sun; Chengjun Li (Journal of Mountain Science, 2012)